The Evolution of Prognostic Factors in Multiple Myeloma. (21st February 2017) - Hanbali, Amr; Hassanein, Mona; Rasheed, Walid; Aljurf, Mahmoud; Alsharif, Fahad
Abstract : Multiple myeloma (MM) is a heterogeneous hematologic malignancy involving the proliferation of plasma cells derived by different genetic events contributing to the development, progression, and prognosis of this disease. Despite improvement in treatment strategies of MM over the last decade, the disease remains incurable. All efforts are currently focused on understanding the prognostic markers of the disease hoping to incorporate the new therapeutic modalities to convert the disease into curable one. We present this comprehensive review to summarize the current standard prognostic markers used in MM along with novel techniques that are still in development and highlight their implications in current clinical practice.